Case Report: A Case of Concomitant Paroxysmal Kinesigenic Dyskinesia and Epilepsy: Can We Treat Two Birds With One Stone? - Geng, Jun-Hong; Zheng, Yang; Li, Quan-Fu; Hou, Qun; Wang, Xiao-Hang; Jiang, Yan (Frontiers in Neurology, 2022)
Background Paroxysmal kinesigenic dyskinesia (PKD) is characterized by recurrent episodes of movement-induced motor attacks. PKD patients may have concomitant epilepsy. Differentiation between the two disorders and effective control of both diseases remain challenging. Case Presentation We present a Chinese girl with typical manifestations of PKD, who also suffered from generalized tonic-clonic seizure attacks at the same time. Genetic testing confirmed a PRRT2 mutation (c.649dupC). Oxcarbazepine was initially used, but withdrawn due to a hypersensitivity reaction. Levetiracetam was initiated afterwards, which was effective for seizures but failed to control her PKD symptoms. The addition of lacosamide (LCM) completely controlled her PKD symptoms. Conclusion This is the first case reporting the effectiveness of LCM for concomitant PKD and epilepsy. Our case proposes a novel alternative for such patients who are resistant or cannot tolerate conventional anti-sodium antiepileptics.